Predictive and prognostic factors in patients with blood-culture-positive community-acquired pneumococcal pneumonia. Issue 3 (12th May 2016) - Amaro, Rosanel; Liapikou, Adamantia; Cilloniz, Catia; Gabarrus, Albert; Marco, Francesc; Sellares, Jacobo; Polverino, Eva; Garau, Javier; Ferrer, Miquel; Musher, Daniel M.; Torres, Antoni
In patients with pneumococcal community-acquired pneumonia (CAP), the risk factors for bacteraemia and its impact on outcomes are not fully elucidated. We aimed to compare characteristics of patients with blood-culture-positive versus blood-culture-negative pneumococcal CAP, and to characterise bacteraemic serotypes. We describe a prospective, observational study on nonimmunocompromised patients with pneumococcal CAP, from 1996 to 2013. We define severe pneumonia according to American Thoracic Society/Infectious Diseases Society of America guidelines. Of a total of 917 patients with pneumococcal CAP, 362 had blood-culture-positive pneumococcal pneumonia (BCPPP; 39%). High C-reactive protein (CRP) (≥20 mg·dL −1 ) (odds ratio (OR) 2.36, 95% CI 1.45–3.85), pleural effusion (OR 2.03, 95% CI 1.13–3.65) and multilobar involvement (OR 1.69, 95% CI 1.02–2.79) were independently associated with bacteraemic CAP, while nursing home resident (OR 0.12, 95% CI 0.01–1.00) was found as a protective factor. Despite the clinical differences, BCPPP showed similar outcomes to blood-culture-negative pneumococcal pneumonia (BCNPP). 14% of the serotypes (period 2006–2013) causing bacteraemia are included in pneumococcal conjugate vaccine PVC7, 74% in pneumococcal conjugate vaccine PVC13 and 83% in pneumococcal polysaccharide vaccine PPSV23. Pleural effusion, a high level of CRP and multilobar involvement predicted an increased risk of BCPPP. Although BCPPP patients were more severely ill at admission, mortality was not significantly greater than in BCNPP patients. Pleural effusion, multilobar involvement and CRP ≥20 mg·dL –1 indicate high risk of bacteraemic pneumococcal pneumonia http://ow.ly/4mJk2Z